Rancang Bangun Aplikasi Informasi Wisata Kabupaten Indramayu Berbasis Mobile Android - Mohammad Kaiman Maulidani; Darsanto; Muhammad Edi Iswanto (NUANSA INFORMATIKA, 2024)
Indramayu Regency in West Java has substantial potential in the tourism sector, which can bolster the region's economic growth. However, the dissemination of information about tourist attractions in Indramayu is limited, necessitating the creation of an application to simplify the search for tourism data and information. This study successfully designed and developed an Android-based mobile application named Wisayu using the Rapid Application Development (RAD) method to create a fast, efficient, and user-friendly app. The application was tested in two phases: alpha testing and beta testing. Alpha testing employed blackbox and whitebox methods, yielding valid results. Beta testing was divided into two parts: quantitative data analysis for validity and reliability testing, and descriptive statistical analysis using the User Experience Questionnaire (UEQ). The quantitative data analysis revealed that 22 out of 26 indicators were valid, with Pearson Product Moment correlation values exceeding the r table value of 0.33, while the remaining 4 indicators were below the r table value. The Cronbach's Alpha value for the 26 questionnaire items was 0.63, indicating good reliability. Descriptive statistical analysis showed positive evaluations in each UEQ dimension, with attractiveness scoring 1.32, pragmatic quality 1.63, and hedonic quality 1.11, demonstrating that the application was well-received by users.